A North-South comparison of education and training systems: Lessons for policy - Emer Smyth; Anne Devlin; Adele Bergin; Séamus McGuinness (The Economic and Social Research Institute (ESRI), 2022)
This study draws on international and national survey data, administrative data, 31 interviews with 35 policy stakeholders and input from a consultation with stakeholders to document commonalities and differences between the education systems in Ireland and Northern Ireland. Remarkably, it is the first study to systematically compare the systems from primary to tertiary levels and it is hoped that the findings will provide insights for future policy learning in both jurisdictions. The study is timely given the independent review of education being conducted in Northern Ireland and ongoing reviews, especially at primary and upper secondary levels, in Ireland.
Keywords: 330; Bildungswesen; Bildungsniveau; Bildungsertrag; Bildungsinvestition; Irland; Nordirland